If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8y + 7)(8y + 27) = 0 Reorder the terms: (7 + 8y)(8y + 27) = 0 Reorder the terms: (7 + 8y)(27 + 8y) = 0 Multiply (7 + 8y) * (27 + 8y) (7(27 + 8y) + 8y * (27 + 8y)) = 0 ((27 * 7 + 8y * 7) + 8y * (27 + 8y)) = 0 ((189 + 56y) + 8y * (27 + 8y)) = 0 (189 + 56y + (27 * 8y + 8y * 8y)) = 0 (189 + 56y + (216y + 64y2)) = 0 Combine like terms: 56y + 216y = 272y (189 + 272y + 64y2) = 0 Solving 189 + 272y + 64y2 = 0 Solving for variable 'y'. Factor a trinomial. (27 + 8y)(7 + 8y) = 0Subproblem 1
Set the factor '(27 + 8y)' equal to zero and attempt to solve: Simplifying 27 + 8y = 0 Solving 27 + 8y = 0 Move all terms containing y to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 8y = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 8y = 0 + -27 8y = 0 + -27 Combine like terms: 0 + -27 = -27 8y = -27 Divide each side by '8'. y = -3.375 Simplifying y = -3.375Subproblem 2
Set the factor '(7 + 8y)' equal to zero and attempt to solve: Simplifying 7 + 8y = 0 Solving 7 + 8y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 8y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 8y = 0 + -7 8y = 0 + -7 Combine like terms: 0 + -7 = -7 8y = -7 Divide each side by '8'. y = -0.875 Simplifying y = -0.875Solution
y = {-3.375, -0.875}
| 4(3x-2)=6(4x-2) | | 27=5+9(x+8) | | 7+2(b-3)=-9 | | 2x^2-6x-8=8 | | x(5x+3)=2x^2-5x+3 | | 62-x=281 | | -7-9x=-61g | | x=13/8 | | 0.2(4x+32)=0.8(x+8) | | 2-x+9=8 | | 151-y=260 | | 13/8= | | -4+y=-0.5x | | 3=7(y-7) | | 6c+24=4c-1 | | 200W^2+W-20=0 | | 256=18-x | | 15a+16a+7a= | | 7x-27=-22 | | 7x+2y=190 | | 2z-8=7z+9 | | 18=.32w | | (s-8)+5=10 | | 5-x-2=5 | | 9x+8=9(x+1) | | 8-2x=7+3x | | 3x+6y=304 | | y=-9x+15 | | 8/8=13/8 | | 7x+1=3x-35 | | 5=.05w | | 16+8b=4(5b-5) |